Pharmacists' knowledge, attitudes, and perceived barriers to cancer pain management: a cross-sectional survey in Chongqing, China - Yu Liu; Tao Chen; Xinyu Li; Jie Song; Fujun Zhang (BMC Health Services Research)
Abstract Background The role of pharmacists in multidisciplinary cancer pain management teams is increasingly being recognized in Chinese medical practice. However, given the large number of patients, there is still a shortage of pharmacists with the necessary knowledge and skills. This study assessed pharmacists' attitudes and competencies in cancer pain management, identified major barriers in China, and provided evidence for the development of targeted interventions. Methods A cross-sectional questionnaire survey was conducted among pharmacists in secondary and tertiary hospitals in Chongqing, China, from March 1 to May 30, 2022. The questionnaire comprised four parts: basic information about the respondents, their concepts and attitudes toward cancer pain management, an evaluation of their knowledge of pain management, and subjective assessments of their barriers to cancer pain management. Results The survey was conducted in 35 hospitals. The overall correct response rates for the cancer pain treatment concepts and attitudes test were 87.5% and 88.9% for secondary and tertiary hospitals, respectively, with no significant difference (χ2 = 1.189, p = 0.276). The results of the cancer pain treatment knowledge assessment revealed that the correct response rates for pharmacists who had received 0, 1, 2 or more than 3 courses of cancer pain treatment education were 55.7%, 55.0%, 61.4%, and 70.3%, respectively. Compared with that achieved with 0 training sessions, the response rate of the questionnaire under 2 training sessions was significantly different (χ2 = 6.712, p = 0.010), as was the response rate for ≥ 3 training sessions (χ2 = 50.097, p = 0.000). Pharmacists employed in different levels of hospitals or in different positions had similar subjective evaluations of barriers to cancer pain management, with the most commonly identified barriers being insufficient training in cancer pain management, a lack of psychosocial services and a lack of specialized staff for cancer pain management. Conclusions Pharmacists' performance on the cancer pain management knowledge test was below expectations. Inadequate education is a significant barrier to effective cancer pain management. To address this challenge, providing specialized training on cancer pain management for pharmacists is crucial.